A Critical Review on the Book Philosophy of Religious Thought in Islam and Christianity - Sajjad Behruzi; Mohammad Reza Bayat (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Philosophy of Religious Thought in Islam and Christianity in the field of theology is a comparison and compares the structure of Ash'ari Kalam and Catholic theology based on the reading of Thomas Aquinas. The authors of the book have first studied the structure of theological treatises and the origins of Catholic theology by referring to the place of Ash'ari Kalam in Islamic sciences and its historical evolution to be able to compare Ash'ari Kalam and Catholic theology at the level of origins and problem-solving methods. The strengths of this book include: providing extensive information on Ash'ari Kalam and Catholic theology, avoiding mere attention to apparent similarities between Ash'ari Kalam and Catholic theology, and attempting to achieve a common language as the main achievement of the comparison. Some of the weak points of this book are some undocumented explanations, point to some apparent similarities between Islamic Kalam and Protestant theology despite attempts to avoid it, biased judgments, failure to refer to all sources, and failure to follow some rules of the comparative method. Some of the weak points of this translating book are difficulty in reading some passages of the text, ambiguity in translating some sentences, overcoming Arabic idioms, and their lack of explanation.